Effects of Whole-Body Electromyostimulation on Strength-, Sprint-, and Jump Performance in Moderately Trained Young Adults: A Mini-Meta-Analysis of Five Homogenous RCTs of Our Work Group - Wirtz, Nicolas; Dörmann, Ulrike; Micke, Florian; Filipovic, André; Kleinöder, Heinz; Donath, Lars (Frontiers in Physiology, 2019)
Background Whole-body electromyostimulation (WB-EMS) has gained increasing interest in sports within recent years. Objective The aim of the present mini-meta-analysis of 5 recently conducted and published randomized controlled WB-EMS trails of our work group was to evaluate the favorable effects of WB-EMS in comparison to conventional strength training. Methods We included parameter of selected leg muscle´s strength and power as well as sprint and jump performance. All subjects were moderately trained athletes (> 2 training sessions/week, > 2 years of experience in strength training; experimental group (n=58): 21.5 ± 3.3 y; 178 ± 8 cm; 74.0 ± 11 kg; control group (n=54): 21.0 ± 2.3 y; 179.0 ± 9 cm; 72.6 ± 10 kg). The following WB-EMS protocols were applied to the experimental group (EG): 2 WB-EMS sessions/week, bipolar current superimposed to dynamic exercises, 85Hz, 350𝜇s, 70% of the individual pain threshold amperage. The control groups (CG) applied the same training protocols without WB-EMS, but with external resistance. Results In summary, five extremely homogenous studies (all studies revealed an I² = 0%) with 112 subjects in total were analyzed with respect to lower limb strength and power in leg curl, leg extension and leg press machines, sprint - and jump performance. Negligible effects with very low within-analyses heterogeneity were found for Fmax of leg muscle groups (SMD: 0.11 (90% CI: -0.08, 0.33), p = 0.73, I² = 0%) and for CMJ (SMD: 0.01 (90% CI: -0.34, 0.33), p = 0.81, I² = 0%). Small effects, also with low heterogeneity were found for linear sprint (SMD: 0.22 (90% CI: -0.15, 0.60), p = 0.77, I² = 0%) in favor of the EMS-group compared to CON. Conclusion We conclude that WB-EMS is a feasible complementary training stimulus for performance enhancement. However, additional effects on strength and power indices seem to be limited and sprint and jump-performance appear to be benefiting only slightly. Longer training periods and more frequent application times and a slightly larger stimulus could be investigated in larger samples to further elucidate beneficial effects of WB-EMS on performance parameters in athletes.